1996
DOI: 10.1172/jci118973
|View full text |Cite
|
Sign up to set email alerts
|

Glanzmann thrombasthenia. Cooperation between sequence variants in cis during splice site selection.

Abstract: Glanzmann thrombasthenia (GT), an autosomal recessive bleeding disorder, results from abnormalities in the platelet fibrinogen receptor, GPIIb-IIIa (integrin ␣ IIb ␤ 3 ). A patient with GT was identified as homozygous for a G → A mutation 6 bp upstream of the GPIIIa exon 9 splice donor site. Patient platelet GPIIIa transcripts lacked exon 9 despite normal DNA sequence in all of the cis -acting sequences known to regulate splice site selection. In vitro analysis of transcripts generated from mini-gene construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 72 publications
0
37
0
5
Order By: Relevance
“…Furthermore, recent studies have demonstrated that sequences not located at the intron/exon borders, regulate the RNA splicing process. 28 These include several silent exonic polymorphisms [29][30][31][32][33] which do not confer an amino acid change.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have demonstrated that sequences not located at the intron/exon borders, regulate the RNA splicing process. 28 These include several silent exonic polymorphisms [29][30][31][32][33] which do not confer an amino acid change.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidences for involvement of genetic polymorphisms in complex disorders as they can affect the functions of genes by altering characteristics such as the expression level, altering DNA binding sites, mRNA stabilization, splicing and folding (Jin et al, 1996;Duan et al, 2003;Chen et al, 2006). For the rs10,046 polymorphism of CYP19gene, the exact functional activity is not clearly understood, and it seems not to have an autonomous function, but it has been claimed that in conjunction with other polymorphisms, the rs10,046 polymorphism may influence the levels of mRNA and its stability (Bampali et al, 2015), so it can be associated with altered levels of the aromatase enzyme and affected estrogen metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…A number of these mutations do not alter consensus splice sites or generate missense or nonsense mutations, yet do affect splice site selection (32,33). These mutations may cause skipping of exon(s) by disrupting the splicing enhancer(s).…”
Section: Discussionmentioning
confidence: 99%